Experimental and numerical investigation on reinforced-concrete slab-beam assemblies exposed to extended and travelling fires. (1st August 2022) - Wang, Yong; Bu, Yixiang; Huang, Zhaohui; Gu, Aolin; Han, Guanxu; Zhang, Xiaoyue; Zhang, Yajun; Liu, Yunli; Chen, Zhenxing; Guo, Wenxuan
Highlights: Tests were conducted to investigate the fire behaviour of four slab-beam assemblies. The influence of travelling fire scenario, support conditions, and reinforcement ratio and layout was investigated. The support conditions of the interior beam greatly influence the deflection magnitude of the heated panels. The maximum internal forces of the tested specimens occurred during the cooling stages. Abstract: In this study, four RC specimens representing as many two-bay slab-beam assemblies were tested under two fire scenarios (extended fire and travelling fire) to investigate the interaction between the rectangular slab and the supporting beam positioned along the short median of the slab (interior beam). The primary focus was on the effects that the fire scenario, reinforcement layout, steel ratio and support conditions along the interior beam may have on the structural behaviour during a fire. The test results include the thermal field, deflections, crack patterns, and failure modes of both slabs and supporting beams. Moreover, finite-element modelling was also used within the framework of ABAQUS to better understand the mechanical behaviour of the specimens throughout the loading process. The results reveal that the flexural stiffness of the vertical support offered by the interior beam has a more prominent influence on deflections, crack patterns, and behaviour during a fire than the steel ratio, reinforcement layout, and fire scenario (extended fire or travelling fire). Furthermore, the numerical results reveal that the highest temperatures and the largest internal forces in the two bays occur during the cooling phase, primarily because of the thermal inertia of the slab, which affects the interaction among the various structural members as well as the load redistribution. Consequently, delayed failure of the assembly may occur during the cooling phase or even after the cooling phase under residual conditions.